A Case of Chromoblastomycosis Caused by Fonsecaea pedrosoi Successfully Treated by Oral Itraconazole Together with Terbinafine - Xu-Cheng Shen; Xiang-Nong Dai; Zhi-Min Xie; Ping Li; Sha Lu; Jia-Hao Li; Yi Zhang; Xing-Dong Ye (Adis, Springer Healthcare, 2020)
Abstract Patients with chromoblastomycosis (CBM) usually have a history of local skin damage related to outdoor activities, mainly manifested as chronic refractory proliferative pathologic changes. We report a case of a 56-year-old man with CBM, identified as Fonsecaea pedrosoi infection by fungal culture and gene sequencing. This patient was successfully treated with a regimen of oral itraconazole (ITZ) and terbinafine lasting 7 months. Through in vitro drug sensitivity tests, minimum inhibitory concentrations of amphotericin, ITZ, and terbinafine were 1 μg/ml, 0.25 μg/ml, and 1 μg/ml, respectively. In this case, terbinafine was found to be more effective than ITZ.